2023
DOI: 10.1111/1759-7714.15151
|View full text |Cite
|
Sign up to set email alerts
|

Predicting visceral pleural invasion in lung adenocarcinoma presenting as part‐solid density utilizing a nomogram model combined with radiomics and clinical features

Fen Wang,
Xianglong Pan,
Teng Zhang
et al.

Abstract: BackgroundTo develop and validate a preoperative nomogram model combining the radiomics signature and clinical features for preoperative prediction of visceral pleural invasion (VPI) in lung nodules presenting as part‐solid density.MethodsWe retrospectively reviewed 156 patients with pathologically confirmed invasive lung adenocarcinomas after surgery from January 2016 to August 2019. The patients were split into training and validation sets by a ratio of 7:3. The radiomic features were extracted with the aid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The calibration curve demonstrated the model's predicted probabilities to be in acceptable agreement with the actual probability, while the DCA illustrated that the combined model provided more net benefit than both the clinical model and the radiomics model. There were several previous studies on predicting VPI status in lung adenocarcinoma by CT-based radiomics features [27][28][29][30][31][32]. Compared with previous studies, our study has some innovative points in patient enrollment and research methods.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The calibration curve demonstrated the model's predicted probabilities to be in acceptable agreement with the actual probability, while the DCA illustrated that the combined model provided more net benefit than both the clinical model and the radiomics model. There were several previous studies on predicting VPI status in lung adenocarcinoma by CT-based radiomics features [27][28][29][30][31][32]. Compared with previous studies, our study has some innovative points in patient enrollment and research methods.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have demonstrated that incorporating radiomics features from the peritumoral region into modeling analysis can enhance predictive accuracy in the preoperative assessment of pathological invasiveness [17], lymphovascular invasion [18], lymph node metastasis [25], and spread through air space in lung cancer patients, compared to models relying solely on intratumoral features [26]. While previous investigations have successfully applied radiomics for assessing VPI status in early lung cancer [27][28][29][30][31][32], their primary focus has been on intratumoral features, with limited exploration of the potential contribution of peritumoral radiomics features. Additionally, the reliability and reproducibility of these models have not been validated in external sets.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies tried to predict an extended panel of histological characteristics using radiomics and AI. Some of them included visceral pleural invasion [41], EGFR mutation [42], and PD-L1 expression [43]. Results are still experimental and their utility in preoperative evaluation of patients is currently debated.…”
Section: Radiomics Modelmentioning
confidence: 99%